On a Quest for a Better Humanity: Introductory Elements for a Deconstructive Reading of Paul Auster’s The Music of Chance - Taali, Anita (European Scientific Journal, ESJ, 2018)
In The Music of Chance, Paul Auster establishes his postmodern appropriation of Sartrean existentialism. His protagonist has been subject to a number of literary studies: while some critics believe him to be an existentially conceived postmodern agent, others have considered him to be the embodiment of the American myth or a Bakhtinean picaro. However, this paper addresses the question of this protagonist’s multifaceted identity. Through the application of Derrida’s deconstruction to a set of binary oppositions in Auster’s narrative, this study aims to prove that not only we cannot attribute one singular meaning to the narrative, but also no singular identity can be ascribed to the protagonist. By deconstructing the binary oppositions of chance/choice, freedom/responsibility, and absurdity/meaning, this thesis attempts to prove that neither does a hierarchical superiority exist in any of the opposing ideas nor can they be ultimately defined as contradictory. Hence, the clear-cut meaning behind the narrative and specifically the protagonist’s actions are questioned. This study concludes that Auster, through the amalgamation of postmodernism and existentialism, has created a protagonist of multifaceted identity, or, a postmodern absurd hero: an absurd hero who finds his own meaning amidst the absurdity of the world, realizes the value of his reaction to contingent occurrences as his choice, and eventually finds his freedom in the responsibility he takes for these choices. Auster’s innovation in this novel is creating a postmodern hero on his existential quest for identity who rises amidst the absurdity of the world. The results of this study suggest that through this creation, Auster aims to guide the readers towards a better humanity in the contemporary postmodern era.